A stability-indicating reverse phase-HPLC method development and validation for newly approved drug, Belzutifan in bulk and pharmaceutical dosage forms - Dumpala Sravya, Banoth Ramya Kuber (Journal of Applied Pharmaceutical Science, 2023)
Belzutifan is a newly approved anti-neoplastic medication that inhibits hypoxia inducible factor through a binding mechanism and stops cellular proliferation. In the present work, a simple, robust, accurate, rapid, reproducible, and stability-indicating reverse phase-high performance liquid chromatography method has been established for the estimation of Belzutifan in bulk and pharmaceutical dosage forms. Belzutifan was eluted from an Agilent C18 (150 mm × 4.6 mm × 5 μ) column at 30°C. Isocratic elution was performed using the mobile phase having Acetonitrile and 0.1% Formic acid and (50:50 v/v). The flow rate was maintained at 1.0 ml/minute and the maximum wavelength for column effluents was detected at 268 nm using a photo diode array detector. The developed method has shown elution at 2.314 minutes. The whole analytical method validation was done satisfactorily as per International Conference on Harmonization regulations. The recovery studies were performed at levels of 50%, 100% and 150%. The percent recovery results were in the range of 99.17%–100.70%. The current method’s regression coefficient of 0.999 showed that it was linear at concentrations between 5 and 30 μg/ml. The limit of detection and limit of quantification values were determined as 0.29 and 0.88. The % relative standard deviation results were seen to be
Keywords: Belzutifan, reverse phase- HPLC, stability indicating, validation, isocratic